Hydration‐Facilitated Fine‐Tuning of the AIE Amphiphile Color and Application as Erasable Materials with Hot/Cold Dual Writing Modes. Issue 25 (13th November 2019) - Jin, Hongjun; Li, Hongpeng; Zhu, Zhiyang; Huang, Jianbin; Xiao, Yunlong; Yan, Yun
Abstract: Hydration water greatly impacts the color of inorganic crystals, but it is still unknown whether hydration water can be utilized to systematically manipulate the emission color of organic luminescent groups. Now, metal ions with different hydration ability allow fine‐tuning the emission color of a fluorescent group displaying aggregation induced emission (AIE). Because the hydration water can be removed easily by gentle heating or mechanical grinding and re‐gained by solvent fuming, rewritable materials can be fabricated both in the hot‐writing and cold‐writing modes. This hydration‐facilitated strategy will open up a new vista in fine‐tuning the emission color of AIE molecules based on one synthesis and in the design of smart luminescent devices. Abstract : Just add water : Hydration water on metal ions can be utilized to reversibly fine‐tune the emission color of organic luminescent groups for aggregation induced emission. The hydration water can be removed by heating or mechanical grinding and re‐gained by solvent fuming.